Analysis of Sustainable Tourism Destination Development for Digital Nomads (Comparative Study: Lisbon-Portugal and Canggu, Bali-Indonesia) - Mariati, Sri; Gilitasha, Andre; Rahmanita, Myrza; Djati, Sundring Pantja; Adawiyah, Robiatul (Technium Social Sciences Journal, 2023)
The digital nomad is a brand-new traveler that has emerged as a result of the digital age. These travelers are able to work while constantly travelling from one location to another and simply need an internet connection. They continue to earn money as they travel. The most popular destinations for digital nomads in the world are Lisbon, Portugal, and Canggu-Bali, Indonesia. By comparing the characteristics of digital nomads who travel to Canggu and Lisbon, this study hopes to identify differences in the standards of sustainable tourism destinations (Accessibility, Attractions, Amenities, Activities, and Accommodations). Involving sixty participants, this quantitative study was undertaken. The findings show that there are considerable differences in the two locations’ features, specifically the education level of digital nomad tourists, and between the three factors, namely accessibility, amenities, and accommodation. Lisbon excels in the accessibility and amenities component of the distinctions, while Canggu shines in the accommodation component. Canggu also shines in terms of lower living costs that complement the expensive digital nomad lifestyle, which attracts travelers who are interested in it. The development of Lisbon’s tourism locations must also focus primarily on the elements of facilities, activities, and accommodation. The development of tourist locations in Canggu, however, might concentrate on the elements of accessibility, attractions, and amenities.